10 years – from Gomel Secondary Fire-Technical School to Gomel Engineering Institute - Ukrainets, Александр Анатольевич (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
Gomel Engineering Institute of the Ministry for Emergency Situations of the Republic of Belarus is the successor of Gomel Secondary Fire-Technical School of Chief directorate of the militarized fire service of the Ministry of Internal Affairs of Belarus created by the order of the Ministry of Internal Affairs of the Republic of Belarus №. 020 dated May, 21, 1997. In the work questions of organization of teaching and educational process, scientific research activity and system of professional selection of the future workers of units and divisions on the extreme situations are considered. Given approach allows attracting youth to edu-cational institutions of the Ministry for Emergency Situations and may raise prestige of the profession of the rescue-engineer.